Improved vaccination coverage after two rounds of multi-antigenic catch-up vaccination in Mauritania. - Maider Pagola-Ugarte; Ankur Rakesh; Julita Gil-Cuesta; David Kidinda; Thierno Moctar Kelly; Sidi Zahaf; Mohamed Mahmoud O Ely Mahmoud; Mohamedou O Mohamed Salem; Mbareck Houmeid; Dah Cheikh; Naceredine Ouldzeidoune; Catherine Bachy (Public Library of Science (PLoS), 2024)
Although Mauritania carried out its Expanded Programme on Immunization (EPI), in 2015 the goal of vaccination coverage (VC) remained unmet in Bassikounou district and Mbera camp, contexts with large migrant populations. In response, during 2018, the national authorities, together with Médecins Sans Frontières organised two rounds of multi-antigenic mass vaccination campaigns (2RMASVC). The campaigns included oral polio (OPV), pneumococcal (PCV13), pentavalent and rotavirus vaccines for all eligible children six weeks to 59 months old. This study describes the results of the 2RMASVC. Cross-sectional household VC surveys (VCS1 and VCS2) were conducted before and after the 2RMASVC. Data were collected on vaccination status according to self-reporting and vaccination cards, and on reasons for non-vaccination (RNV). In total, 4,569 children received at least one dose of vaccine in the first round and 5,602 children in the second. Baseline VC, as fully vaccinated, according to VCS1, was 59.9% of children 12 to 59 months in Bassikounou district and 65.8% in Mbera camp. After the 2RMASVC, the coverages increased to 84.7% and 75.9% respectively. Absence from home, lack of motivation, late initiation of vaccinations and lack of awareness about vaccination were the main RNV during the 2RMASVC. Although the 2RMASVC did not reach its goal of 90%-95% VC, the strategy significantly increased VC in the two settings for children aged 12 to 59 months. Therefore, this catch-up approach could be considered to improve VC of children who miss out of the EPI strategy in resource-limited settings.